2022
DOI: 10.21037/jgo-22-471
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 receptor-associated kinase 1 participates in the modulation of the NLRP3 inflammasome by tumor-associated macrophages in hepatocellular carcinoma

Abstract: Background: Hepatocellular carcinomas (HCCs) occur frequently in the digestive system and are associated with high mortality. This current study examined the regulatory relationship between interleukin (IL)-1 receptor-associated kinase 1 (IRAK1), NLR family pyrin domain-containing 3 (NLRP3) inflammasomes, and tumor-associated macrophages (TAMs) in the growth and metastasis of HCC. Methods:The expression of IRAK1 and NLRP3 was assessed in tissues and cells via quantitative real-time polymerase chain reaction (q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Several lncRNAs and miRNAs can exert immunosuppressive influence to facilitate HCC progression, such as lncMALAT1 ( 72 ), lncHULC ( 73 ), lncHOTAIR ( 74 ), lncLINC01132 ( 75 ), lncPVT1 ( 76 ), lncLINC00662 ( 77 ), lncβ-Catm ( 78 ), miR-23a-3p ( 79 ), and miR-146a-5p ( 80 ). Dysregulated expression of epigenetic regulators, including DNMT3α ( 81 ), KDM1A ( 82 , 83 ), YTHDF2 ( 84 ), and RALYL ( 85 ), as well as kinases and phosphatases such as IRAK1 ( 86 ) and SHP2 ( 87 ), may also contribute to the formation of an immunosuppressive TME in HCC. As an intricate malignancy, HCC is characterized by metabolic reprogramming, in which glycolytic and lipid metabolism aberrations can contribute to an immunosuppressive TME.…”
Section: General Concept Of Cancer Stem Cellsmentioning
confidence: 99%
“…Several lncRNAs and miRNAs can exert immunosuppressive influence to facilitate HCC progression, such as lncMALAT1 ( 72 ), lncHULC ( 73 ), lncHOTAIR ( 74 ), lncLINC01132 ( 75 ), lncPVT1 ( 76 ), lncLINC00662 ( 77 ), lncβ-Catm ( 78 ), miR-23a-3p ( 79 ), and miR-146a-5p ( 80 ). Dysregulated expression of epigenetic regulators, including DNMT3α ( 81 ), KDM1A ( 82 , 83 ), YTHDF2 ( 84 ), and RALYL ( 85 ), as well as kinases and phosphatases such as IRAK1 ( 86 ) and SHP2 ( 87 ), may also contribute to the formation of an immunosuppressive TME in HCC. As an intricate malignancy, HCC is characterized by metabolic reprogramming, in which glycolytic and lipid metabolism aberrations can contribute to an immunosuppressive TME.…”
Section: General Concept Of Cancer Stem Cellsmentioning
confidence: 99%
“…Many studies have shown that the NLRP3 inflammasome has a promoting effect on HCC. NLRP3 has been found highly expressed in HCC tissues, and inhibition of NLRP3 inflammasome activation could induce apoptosis and regulate the levels of inflammatory factors, which would suppress the growth of HCC cells (Chen et al, 2022) (Li et al, 2020a). Knockout of NLRP3 in HCC cells also inhibited tumor growth and metastasis in vivo, as well as increased the sensitivity to NK cell cytotoxicity (Lee et al, 2021).…”
Section: The Research Of Nlrp3 In Hepatocellular Carcinomamentioning
confidence: 99%
“…The surface antigen CD68 is a specific surface marker for monocyte macrophages, including Kupffer cells. Flow cytometry and immunohistochemistry are used to detect the number and distribution of macrophages, which can reveal Hao2 hepatocellular carcinoma and the distribution pattern of HCC [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%